Effect of hearing loss on cognitive function in patients with mild cognitive impairment: A prospective, randomized, and controlled study - Tong, Jie; Zhang, Jie; Xu, Luli; Liu, Meiling; Min, Jie; Yao, Miaomiao; Cheng, Xiaoyan; Zhang, Qi; Sun, Xirong; Yuan, Jie (Frontiers in Aging Neuroscience, 2022)
Background: Hearing loss (HL) may increase the risk of cognitive decline in the elderly. However, the randomized controlled study on the effect of HL on cognitive function in mild cognitive impairment (MCI) is very limited. Methods: From November 1, 2020, to March 30, 2022, 1987 individuals aged 55 to 65 years were randomly divided into the MCI-HI, MCI-nHI, and nMCI groups by stratified sampling, with 30 participants in each group. Mini-mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), Pure Tone Audiometry (PTA), and Auditory Brainstem Response (ABR) were measured at baseline and at a follow up 12 months later. The trial protocol was registered with ClinicalTrials.gov with the number NCT05336942. Results: Among the 90 participants, the average age was 60.41±6.48. In MCI-HI group at baseline, the PTA score of both ears was negatively correlated with the naming and memory score (p<0.05), and the PTA score of both ears was negatively correlated with the MoCA and abstraction score at the 12-month follow-up (p<0.05). However, there were no significant differences among the PTA, ABR, MMSE, and MoCA scores in the MCI-nHI and nMCI groups (p>0.05). Regression analysis showed that the PTA score of the right ear at baseline was an important factor associated with the MoCA, visuospatial/executive, naming, and ab-straction scores at the 12-month follow-up (β=-0.776 to -0.422, p<0.05). Conclusions: HL was significantly negatively associated with cognitive function only in patients with MCI with hearing impairment (HI), and the PTA of the right ear may be a predictor of cognitive decline after one year in patients with MCI with HI. This information may help primary health care clinicians prevent MCI by screening and intervening in care for elderly patients with HL.